Player load, acceleration, and deceleration during forty-five competitive matches of elite soccer - Dalen, T.; Jørgen, I.; Gertjan, E.; Geir Havard, H.; Ulrik, W. (The Journal of Strength and Conditioning Research, 2016)
The use of time-motion analysis has advanced our understanding of position-specific work rate profiles and the physical requirements of soccer players. Still, many of the typical soccer activities can be neglected, as these systems only examine activities measured by distance and speed variables. This study used triaxial accelerometer and time-motion analysis to obtain new knowledge about elite soccer players' match load. Furthermore, we determined acceleration/deceleration profiles of elite soccer players and their contribution to the players' match load. The data set includes every domestic home game (n = 45) covering 3 full seasons (2009, 2010, and 2011) for the participating team (Rosenborg FC), and includes 8 central defenders (n = 68), 9 fullbacks (n = 83), 9 central midfielders (n = 70), 7 wide midfielders (n = 39), and 5 attackers (A, n = 50). A novel finding was that accelerations contributed to 7-10% of the total player load for all player positions, whereas decelerations contributed to 5-7%. Furthermore, the results indicate that other activities besides the high-intensity movements contribute significantly to the players' total match workload. Therefore, motion analysis alone may underestimate player load because many high-intensity actions are without a change in location at the pitch or they are classified as low-speed activity according to current standards. This new knowledge may help coaches to better understand the different ways players achieve match load and could be used in developing individualized programs that better meet the "positional physical demands" in elite soccer.